(untitled) (Scientific journal of the Fergana State University, 2024)
This article talks about the important role of mathematical thinking in solving examples and problems related to mathematics, and gives several tasks that students of elementary school should solve based on logical thinking. The solutions of the assigned tasks are indicated. The role of mathematical examples in the development of mathematical thinking of elementary school students is considered important. The main goal of developing mathematical thinking is to help students develop logical and critical thinking. This article provides ways to use practical problems to develop the mathematical thinking of elementary school students. In addition to problems, it is possible to develop mathematical thinking by creating problems. With the help of the given problems, it will be possible to develop the mathematical thinking and mathematical outlook of elementary school students. With the help of these problems, it is appropriate to increase the knowledge of elementary school students by connecting mathematics with other subjects.